PROBLEMATIKA PELAKSANAAN PEMBIAYAAN AR-RAHN DENGAN AKAD AL-QARDH PADA PT. BANK SYARIAH MANDIRI KANTOR CABANG PEMBANTU PETISAH - IVO FARAH ZARA (PREMISE LAW JURNAL, 2015)
The problems faced by PT. Bank Syariah Mandiri KCP Petisah in implementing ar-rahn financing with al-qardh contract were as follows: first, there was no synchronization between the Edict of the National Sharia Board No. 26/DSN-MUI/III/2002 and the implementation of ar-rahn financing with al-qardh contract; secondly, there was the social problem about people’s ignorance in the concept of ar-rahn financing with al-qardh contract which was in line with the Islamic law; thirdly, there was the company’s management problem about the adjustment to sharia financial institution caused by the changing in regulation in ar-rahn financing. Some factors which became the obstacles in implementing ar-rahn financing with al-qardh contract from the internal factors of the company’s management were the lack of understanding of pawn personnel who offered the product of ar-rahn financing to the people, their carelessness in assessing the genuineness of the clients’ gold, and the adjustment to the management o f sharia financial institution as the result of the regulation in ar-rahn financing, according to the Circulation Letter o f Bank Indonesia No. 14/7/DPbs, on February 29, 2012 on qardh with gold as collateral. From the external factors, there were two aspects: judicially, there was no synchronization in the regulation of ar-rahn financing with al-qardh contract, and sociologically, there was no good faith from the clients since some of them pawned imitation gold, and people’s ignorance in the concept of ar-rahn financing according to the Islamic law. Some attempts by PT. Bank Syariah Mandiri KCP Petisah to cope with the problems were by implementing due diligence, adjusting the regulation of ar-rahn financing to the regulation of Bank Indonesia, implementing SOP ar-rahn object analysis, providing training for ar-rahn financing personnel, and conducting operational principle more consistently. Keywords: Qardh Contract, Rahn, Problem, Sharia Bank